(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Writers do advocate change as simplya friendly request however it remains a confined area. In today’s reality, there are women though uneducated yet who might never give up. These writers do not really focus on any person going through mental issues, rather they focus on empowering women by describing accounts of gutsy women, showing them as guides to battle against the direcircumstances of their life. Though each of thenarratives need not have a methodology yet most narratives do have one. Innovative systems are not needed each time rather each portrayal must reach to the spirit of the perusers. The women writers whom I have chosen for my work have taken up issues identified with the situation/s with women in India. It is worth focusing that women have in enormous number taken up their pen since it has permitted them to make their own reality. It has permitted them to set the states of their presence/s, liberated from the immediate impedance of men. Therefore this composing turns into a protected spot from where they can investigate a wide scope of involvement fiction by women writers establishing a significant section of the contemporary Indian writing in English. All things considered, women despise an equivalent status with men. Indeed, even today a wedded woman who makes too much of her calling or academic career is disapproved of. In the current day literary world, it has led to at least a few incredible women as creative writers in every single Indian language.